High‐Power Laser‐Excited‐Phosphor Suspension in Liquid for Digital Projection. Issue 1 (June 2014) - Li, Kenneth
Abstract Laser excited phosphor has been used to excite phosphor material, producing high intensity light output with smaller etendue than that of LEDs with the same long lifetime. But due to the high intensity of the laser light, phosphor with organic binder burns at low power, which requires the phosphor to be deposited on a rotating wheel in practical applications. Phosphor with inorganic binders, commonly known as ceramic phosphor, on the other hand, does not burn, but efficiency goes down as temperature goes up under high power excitation. This paper describes cooling schemes in sealed chambers such that the phosphor materials using organic or inorganic binders can be liquid cooled for high efficiency operations. Confined air bubbles are introduced into the sealed chamber accommodating the differential thermal expansion of the liquid and the chamber. For even higher power operation suitable for digital cinema, a suspension of phosphor in liquid is described suitable for screen brightness of over 30, 000 lumens. The aging issues of phosphor can also be solved by using replaceable phosphor cartridges.